2020
DOI: 10.1080/02656736.2020.1769869
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between percutaneous and laparoscopic microwave ablation of hepatocellular carcinoma

Abstract: Background: Based on patient and tumor characteristics, some authors favor laparoscopic microwave ablation (LMWA) over the percutaneous approach (PMWA) for treatment of hepatocellular carcinoma (HCC). We compared the two techniques in terms of technique efficacy, local tumor progression (LTP) and complication rates. Study design: A retrospective comparative analysis was performed on 91 consecutive patients (102 HCC tumors) who underwent PMWA or LMWA between October 2014 and May 2019. Technique efficacy at one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
1
14
1
Order By: Relevance
“…In terms of comparing surgical MWA, only the laparoscopic approach ensured a good RF rate. We believe that these results might be due to the fact that smaller-sized CRLM were treated using the laparoscopic approach (10 mm vs. 22.8 mm in an open approach) [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of comparing surgical MWA, only the laparoscopic approach ensured a good RF rate. We believe that these results might be due to the fact that smaller-sized CRLM were treated using the laparoscopic approach (10 mm vs. 22.8 mm in an open approach) [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our study also shows that the site of recurrence is commonly associated with the ablation margins. When MWA is used for liver cancer, recurrence also occurred near the ablation area [5,14]. It's believed to be due to the presence of an in ltrating area around the HAE lesion, which has characteristics of invasive growth similar to that of malignant tumors [15].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indeed reported a lower complication rate and shorter length of stay for laparoscopic compared with percutaneous ablations [37]. One study also reported comparable local tumor progression rates [38].…”
Section: Laparoscopic Approach For Local Ablation Therapymentioning
confidence: 97%